Проектното учење во наставата по англиски јазик како странски во високото образование во Република Северна Македонија - Стевковска, Марија (Филолошки факултет, УКИМ, Скопје, 2020)
INTRODUCTION: Project-based learning (PBL) is a teaching method that organizes learning around projects, which are complex tasks where students explore, solve problems and bring final decisions while being monitored by their teachers. The basic features of PBL include: solving complex and authentic problems, creating final products in the form of projects, team work, multidisciplinary approach, creative and critical thinking, learners’ autonomy, individual teaching approach, communication skills, and new teachers’ roles. These characteristics of PBL make it particularly appropriate for teaching EFL in higher education, as it focuses on students and their needs. Although the number of studies related to PBL implementation in EFL classes has been increasing on a global level, this method has not been fully studied in the Republic of North Macedonia. AIMS: The aims of this research are twofold: 1) to study the possibility of using PBL in EFL classes in higher education in the Republic of North Macedonia in order to deveop all four language skills; and 2) to test whether there is a statistically significant difference in the use of PBL in comparson to traditional language teaching. METHODS: 80 first-year students from the International Balkan University in Skopje participated in the study. They were divided in a control and experimental group. PBL was used in the experimental group. All students were given a pre- and a posttest in all four language skills. The students and the teacher did a survey before and after the study. The obtained data were statistically processed in MS Excel and SPSS v.20.0. They were later analyzed with the dependent t-test and the independent t-test. The p<0,005 was taken as statistically significant. The study was conducted from February to May 2019. RESULTS: Results have shown that there is a statistically significant difference between the mean values of the tests (pretest М=79,97, posttest М=85,37, t= 2,513, p=0,016) in the experimental group, but not in the control group (pretest М=77,52, posttest М=76,67, t=,672, p=0,505). Regarding each language skill in the experimental group there was a statistically significant difference in reading (pretest M=19,77, SD=2,98; posttest M=22,62, SD=2,5, t= - 8,365, p= .000), writing (pretest M=20.1, SD=3,82; posttest M=21.52, SD=3,25, t= - 4,481, p= .000) and speaking (pretest M=20,65, SD=3,01; posttest M=21,26, SD=2.76, t= - 3,871, p= .000), but not in listening (pretest M=19,45, SD=3,5, posttest M=19.6, SD=3,88, t=-0,495 p=0,623). According to results of the survey with the students at the end of the study they had a positive opinon of the PBL and said that it helped them develop their language skills (76% listening, 82% speaking, 44% reading, 76% writing). They identified three main problems: time management, insufficient number of meetings with the group and the teacher, and lack of freedom in the choice of topics. The teacher also reported about students having problems with meeting deadlines, and increased workload outside the classroom. CONCLUSION: The following conclusions can be drawn from the study: PBL yields statistically significant better results in reading and writing, partially in speaking, but not in listening. PBL may successfully be implemented in EFL classes in higher education provided a students’ needs analysis has been conducted and students have been prepared for team work, autonomous learning and alternative assessment. PBL can fully be used if students have a minimum of B1 level. EFL curricula and sillabi in higher education should include elements of EAP and ESP. Teachers need to cooperate with colleagues from other departments or faculties. EFL sillabi cannot be realized through PBL exclusively because of the big number of students and the need for input. Both individual and group work should be used. More credits should be given to project assessment so that students would have a more serious approach towards PBL. Much time should be spent on developing time management skills, team work, and raising students’ collective awareness. Activities should be performed to increase both students’ and teachers’ motivation.
Project-based learning in EFL courses in higher education in the Republic of North Macedonia
Докторска дисертација одбранета во 2020 година на Филолошкиот факултет во Скопје, под менторство на проф. д–р Солзица Поповска.
Keywords: Project-learning, EFL, language skills, traditional teaching